Bound by Bondage : Slavery and the Creation of a Northern Gentry - Maskiell, Nicole Saffold, 1980- (Book collections on Project MUSE., 2022)
"This book traces several elite Anglo-Dutch families back to the founding generations of the Northeastern colonies and follows their growth to the eve of the American Revolutionary War, showing how family power, racial views of mastery, and slaveholding linked a divided Northeast. Examining government documents, runaway slave ads, and letters in both Dutch and English, Maskiell foregrounds the gaze of such captive peoples and argues for a reevaluation of the legacies and narratives of the Northeastern elites who held them in bondage"--